Jejuno-jejunal invagination at the line of the Braun anastomosis - Cetinkaya, Ziya; Girgin, Mustafa; Kocakoc, Ercan; Ayten, Refik (My University, 2007)
Intestinal invagination or intussusception is an uncommon condition in adults. Delayed diagnosis can result in bowel ischemia that can be fatal. A 37-year-old man hospitalized with complaints of abdominal pain, nausea and vomiting. Physical examination revealed a localized muscular defence and a painful palpable mass in the left upper quadrant. He had undergone an antrectomy and Billroth II gastroenterostomy for gastric outlet obstruction 2 years ago and 5 days after this operation, he was diagnosed with acute abdomen (anastomotic leakage?) and cholecystojejunostomy and Braun anastomosis was performed. Preoperative diagnosis established by ultrasonography and computed tomography as invagination. Emergent surgery was performed. The lesion causing invagination was located in efferent jejunum limb of Braun anastomosis towards gallbladder. Reduction was applied to the invaginated bowel segment. The patient was discharged on the postoperatively 7th day. This case illustrates that patients with gastric surgery and small bowel anastomosis, invagination can be occur at the side of this anastomosis. © 2006 Elsevier Ireland Ltd. All rights reserved.
Keywords: Adult; Braun anastomosis; CT; Invagination